The world's greatest detective and her just okay assistant - Tully, Liza, 1956- (Berkley, 2025)
"A great detective's young assistant yearns for glory, but first they must learn how to get along in this delightful feel-good mystery. Olivia Blunt doesn't want to be an assistant detective for the rest of her life. She's determined to learn everything she can from her mentor, renowned investigator Aubrey Merritt--but the latter is no easy grader. After weeks of fielding phone calls from parties pining for the celebrated detective's help, a case comes across Olivia's desk that just might be worthy of Merritt's skills. On the evening of her sixty-fifth birthday party, Victoria Summersworth somehow fell to her death over her balcony railing on the rocky shore of Lake Champlain. She was a happy woman--rich, beloved, in love, and matriarch of the preeminent Summersworth family. The police have ruled it a suicide, but her daughter, Haley, thinks it was murder. Merritt is ever the skeptic, but Olivia believes Haley. Plus, she's desperate to prove her investigative skills to her aloof boss. But the Summersworth family drama is complicated. Olivia realizes she might be in over her head with this whole detective thing . . . or she might be unravelling a mystery even bigger than the one she started with"--